2019
DOI: 10.1002/ece3.5621
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the role of Wolbachia in mtDNA paraphyly and the evolution of unisexuality in Calligrapha (Coleoptera: Chrysomelidae)

Abstract: Calligrapha is a New World leaf beetle genus that includes several unisexual species in northeastern North America. Each unisexual species had an independent hybrid origin involving different combinations of bisexual species. However, surprisingly, they all cluster in a single mtDNA clade and with some individuals of their parental species, which are in turn deeply polyphyletic for mtDNA. This pattern is suggestive of a selective sweep which, together with mtDNA taxonomic incongruence and occurrence of unisexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 87 publications
(128 reference statements)
0
4
0
Order By: Relevance
“…For the majority of the analysed Chrysomelidae, the association with these bacteria is reported in this study for the first time. The presence of reproductive manipulators, such as Wolbachia , in Chrysomelidae is well known (Montagna et al ., 2014; Kajtoch and Kotásková, 2018; Gómez‐Zurita, 2019). These endosymbiotic bacteria are usually abundant in infected species, tending to dominate the community, as observed in this study for four Chrysomelidae species, where Wolbachia represent 94%–99% of the reads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the majority of the analysed Chrysomelidae, the association with these bacteria is reported in this study for the first time. The presence of reproductive manipulators, such as Wolbachia , in Chrysomelidae is well known (Montagna et al ., 2014; Kajtoch and Kotásková, 2018; Gómez‐Zurita, 2019). These endosymbiotic bacteria are usually abundant in infected species, tending to dominate the community, as observed in this study for four Chrysomelidae species, where Wolbachia represent 94%–99% of the reads.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the bacteria associated to leaf beetles were mainly focused on reproductive manipulators (Clark et al ., 2001; Keller et al ., 2004; Kondo et al ., 2011; Roehrdanz and Wichmann, 2013; Montagna et al ., 2014; Krawczyk et al ., 2015; Kolasa et al ., 2017; Takano et al ., 2017; Gómez‐Zurita, 2019), single species of economic importance (Muratoglu et al ., 2011; Chung et al ., 2013; Ali et al ., 2019; Ludwick et al ., 2019; Wang et al ., 2019; Shukla and Beran, 2020) or few strictly related species (Kelley and Dobler, 2011; Montagna et al ., 2015a; Blankenchip et al ., 2018; Wei et al ., 2020). The present study aims to characterize the microbiota associated with a selection of leaf beetle species, representative of the taxonomic diversity and of the various degrees of trophic specialization.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of infection with Wolbachia in Coleoptera varies considerably, depending on the host taxonomy, with Chrysomelidae showing intermediate values ( Kajtoch and Kotásková 2017 ). However, our study precisely focused on two genera, Altica and Calligrapha , which have been shown to have particularly high infection rates with Wolbachia among the leaf beetle groups tested ( Jäckel et al 2013 , Gómez-Zurita 2019 ). Rickettsia has received much less attention than Wolbachia in studies of associations of bacteria with Coleoptera.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is interesting, since it relates this finding with the other only study on Calligrapha endosymbionts, because we know that individuals of Ca. philadelphica in the locality of the study and in the general area are infected by two Wolbachia strains that were named wCalA1 and wCalC2 , with wCalA1 shared with at least three other species, two of them specialized on yet a different host plant, willows ( Gómez-Zurita 2019 ). These data are compatible with the hypothesis that host plants favor shared endosymbiont associations, suggesting a number of interesting ideas, worth testing with a more extensive study.…”
Section: Discussionmentioning
confidence: 99%